Environmental Representation on Australian Children’s Television: An Analysis of Conservation Messages and Nature Portrayals - Breanna L. Morgan; Bradley P. Smith (Conservation)
The early connection children form with nature is vital in fostering positive attitudes towards the environment. Television plays a significant role in shaping these attitudes, yet the inclusion of environmental messaging in children’s programs remains unexplored. This study investigates the extent of conservation messages and nature portrayals on Australian free-to-air children’s television. A mixed-methods approach was employed, analysing all programs airing on ABC Kids, a network aimed at children aged two to six years old, over a seven-day period. Phase 1 involved summarising program descriptions, types, styles, moral themes, and durations. Phase 2 entailed viewing all episodes and noting environmental representations, which were then analysed using content analysis. Only 14.3% of programs (10/70), representing 10.3% of airtime (481/4652 min), included an ‘Environmental Experiences’ moral theme. Content analysis revealed six distinct themes in environmental representations, with more positive than negative messages. These messages were predominantly implicit, conveyed through character dialogue and imagery. Environmental moments represented a balance of flora and fauna but were largely not fact-based. This study suggests a need for increased airtime for environmentally focused programs and more consideration of current environmental issues. Producers are encouraged to include more positive environmental morals and align themes with children’s learning styles to enhance their connection to and understanding of environmental issues.